Back Cover: "Inherently Chiral" Ionic‐Liquid Media: Effective Chiral Electroanalysis on Achiral Electrodes (Angew. Chem. Int. Ed. 8/2017). Issue 8 (26th January 2017) - Rizzo, Simona; Arnaboldi, Serena; Mihali, Voichita; Cirilli, Roberto; Forni, Alessandra; Gennaro, Armando; Isse, Abdirisak Ahmed; Pierini, Marco; Mussini, Patrizia Romana; Sannicolò, Francesco
Abstract : "Inherently chiral" ionic liquids are formed by 1, 1′‐dialkyl‐3, 3′‐bicollidinium salts. As shown by P. R. Mussini, F. Sannicolò et al. in their Communication onpage 2079 ff., they grant outstanding enantioselection for different chiral probes on achiral electrodes even as low‐concentration additives in achiral ionic liquids. The picture shows a bicollidinium hexafluophosphate proudly in action, endowing an ionic liquid medium with chirality, symbolized by the whirlpool, and enantioselectivity, symbolized by the different attraction of ( R )‐ and ( S )‐Me‐DOPA enantiomers towards the vortex.